Utopia of the Other - Rozalski, Maciej (2022)
The text deals with ideas and projects in culture and arts, especially visual arts and performingarts in Brazil aimed at the construction of identity through post-colonial resistance mixed with the modernist utopias of the 20th century. South America, freeing itself from the oppression of the colonial era, had to redefine its national and cultural identity. The utopianbeliefof meeting the Other, the representative of traditional cultures as the bearer of renewal characterizes the search of many artists and thinkers of the 20th century. The experiences of Brazilian modernism, tropicalism, andBrazilian performance bring their version of this perspective, thefigure of the American Indians in various ways. Brazilian art of the 20th century using the concept of symbolic anthropophagy wants to devour Europe. But as contemporary decolonial studies show, Brazilian modernism, transforming the Indian into a rhetorical and aesthetic figure, ends up in this way devouring its own indigenous people. The decolonial concepts and finally the contemporary Amerindian perspective bring their own answer, deconstructing and exposing hidden prejudices of Brazilian culture